Down-regulation of lncRNA LINC00152 Suppresses Gastric Cancer Cell Migration and Invasion Through Inhibition of the ERK/MAPK Signaling Pathway - Shi, Yan (Onco Targets Ther, 2020)
PURPOSE: The aim of this study was to explore the regulatory role and mechanism of long noncoding RNA LINC00152 in gastric cancer (GC) cells. METHODS: LINC00152 expression in GC tissues and cells was detected by reverse transcription-polymerase chain reaction (qRT-PCR). MKN45 and MGC-803 cells were selected and assigned into different groups after transfection with si-LINC00152, activated ERK/MAPK signaling pathway (SA), or negative control. Cell proliferation, apoptosis, cycle, migration and invasion were assessed by CCK-8, flow cytometry, Transwell assay and Scratch test, respectively. Western blot analysis was conducted to detect the expression of E-cadherin, N-cadherin and ERK/MAPK signaling pathway protein. RESULTS: Compared with the normal tissues, higher expression of LINC00152 was found in GC tissues and LINC00152 was remarkably correlative with clinical stage and lymphatic metastasis. LINC00152 expression in GC cells was higher than that in GES-1 cells. Compared with the NC group, the cell proliferation rate, cells in G2/M phase, migration and invasion abilities as well as the expression of N-cadherin and p-ERK-1/2 were significantly decreased, and the expression of E-cadherin, cells in G0/G1 phase and cell apoptosis rate were significantly increased in the si-LINC00152-1 group. ERK/MAPK signaling pathway activator SA could reverse the biological role of LINC00152 in GC cells. CONCLUSION: These results demonstrated that the interference of LINC00152 expression may inhibit the invasion and migration of GC cells by inhibiting the ERK/MAPK signaling pathway.